Evolutionary relationship analysis of STARD gene family and VvSTARD5 improves tolerance of salt stress in transgenic tomatoes. Issue 5 (21st September 2022) - Lu, Shixiong; He, Honghong; Wang, Ping; Gou, Huiming; Cao, Xuejing; Ma, Zonghuan; Chen, Baihong; Mao, Juan
Abstract: The steroidogenic acute regulatory protein‐related lipid transfer domain (STARD) forms a protein that can bind membrane‐derived phospholipid second messengers and plasma membranes. Although it has been reported in many plants, the evolutionary relationship of the STARD gene family has not been systematically analyzed, and functions of the HD‐START and HD‐START‐MEKHLA domain subgroup genes under hormone and abiotic stress are also unclear in grapes. This study identified and analyzed 23 VvSTARD genes, which were distinctly divided into five subgroups according to five conserved domain types. The analyses of codon preference, selective pressure, and synteny relationship revealed that grape had higher homology with Arabidopsis compared with rice. Interestingly, the expression levels of VvSTARD genes in subgroups 1, 2, and 3 exhibited significant upregulation under NaCl treatment at 24 h, but VvSTARD genes in subgroups 4 and 5 were upregulated under methyl jasmonate (MeJA) treatment at 24 h. The subcellular localization showed that VvSTARD5 was localized in the nucleus. Additionally, under NaCl treatment at 24 h, there were an obvious decrease in the relative electrical leakages and the content of malondialdehyde (MDA), while the relative expression level of VvSTARD5 and content of proline were obviously enhanced in three transgenic lines. Therefore, the overexpression of VvSTARD5 greatly increased the salt tolerance of transgenic tomatoes. Collectively, this study preliminarily explores the comprehensive function of the STARD gene family in grapes and verifies the function of VvSTARD5 in response to salt.